Characteristic behaviour of the Portuguese large concrete dams built with granite aggregates and affected by ASR - Batista, A. L. (2016)
In a universe of about sixty large concrete dams monitored in Portugal, there are 19 dams affected by swelling processes already identified. From these, there are 13, where coarse granite aggregates were used in the concrete composition, built between about 1940 and 1980, affected by alkali-silica reactions (ASR), which exhibit a behaviour characterized by very low expansion rates during the first 20 to 30 years, but showing since then increasing rates. Some dams in which this characteristic behaviour occurs are described in the paper, as well as the related structural effects in each one. The monitoring results of the 13 concrete dams, where granite aggregates were used, were obtained with specific devices. They show accumulated expansions of about 200x10-6 and current average free swelling rates of about 10x10-6 per year in most of them. However, there is one case in which the accumulated strain and the current swelling rate reach about 500x10-6 and 25x10-6 per year, respectively. Since the swelling magnitude values are moderate, no problems related with serviceability and safety are expected in the near future. However, the standard tests of accelerated expansion performed on samples taken from the body of some of these dams showed a much lower growth potential than the one recorded on site. For this reason monitoring of these dams and careful analysis of the results should continue.